EMPOWERING THE UMKM COMMUNITY BY IMPLEMENTING COMPETENCY-BASED DIGITAL MARKETING AT LAKE TOBA TOURIST DESTINATION TOBASA DISTRICT - Bunga Aditi; Tapi Rondang Ni Bulan; Olga Theolina Sitorus; Sopi Pentana; Hasminidiarty (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
Community empowerment is carried out in an effort to improve the quality of community welfare. To achieve this goal, it is necessary to create an empowerment program for Micro, Small and Medium Enterprises (MSMEs) by implementing digital marketing as a current requirement in accordance with increasingly sophisticated technological developments. The empowerment program through the implementation of competency-based digital marketing as an effort to promote superior products originating from the Lake Toba tourist destination, meaning that MSME actors in this area must have the ability to use online-based applications to develop their business. The results of the study in general, MSME participants at the Lake Toba Tourism Destination, Toba Regency, were able to participate in activities from implementation to mentoring well. As a suggestion for the implementation of the next activity, it is necessary to emphasize more on what needs to be done by participants.